2022
DOI: 10.3390/jpm12060955
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Severity COVID-19 Assessment in Vaccinated and Unvaccinated Patients: Comparison of the Different Variants in a High Volume Italian Reference Center

Abstract: Purpose: To analyze the vaccine effect by comparing five groups: unvaccinated patients with Alpha variant, unvaccinated patients with Delta variant, vaccinated patients with Delta variant, unvaccinated patients with Omicron variant, and vaccinated patients with Omicron variant, assessing the “gravity” of COVID-19 pulmonary involvement, based on CT findings in critically ill patients admitted to Intensive Care Unit (ICU). Methods: Patients were selected by ICU database considering the period from December 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 120 publications
3
10
0
Order By: Relevance
“…Among which people in UAE country are 100% vaccinated & least vaccinated in Nigeria i.e 13%. Significant differences were observed, with respect to severity of COVID-19 pulmonary involvement, between unvaccinated patients and vaccinated patients affected by Alpha variant, and same was observed between unvaccinated patients and vaccinated patients with Delta variant (1) . Pneumonia due to COVID-19 was present in 78% of unvaccinated patients, but only 41% of fully vaccinated patients (P = .003 for the difference between groups) https://www.indjst.org/ which indicates pneumonia was roughly twice as frequent for unvaccinated compared to fully vaccinated patients (2) .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Among which people in UAE country are 100% vaccinated & least vaccinated in Nigeria i.e 13%. Significant differences were observed, with respect to severity of COVID-19 pulmonary involvement, between unvaccinated patients and vaccinated patients affected by Alpha variant, and same was observed between unvaccinated patients and vaccinated patients with Delta variant (1) . Pneumonia due to COVID-19 was present in 78% of unvaccinated patients, but only 41% of fully vaccinated patients (P = .003 for the difference between groups) https://www.indjst.org/ which indicates pneumonia was roughly twice as frequent for unvaccinated compared to fully vaccinated patients (2) .…”
Section: Discussionsupporting
confidence: 59%
“…COVID-19 was emerged in Wuhan city of China in December 2019. Since 2 years after the first described SARS-CoV-2 patient, the pandemic of COVID-19 is still being continued in many countries with new infection waves (1) . Initially, it was caused by Beta variant of SARS-Cov2 virus.…”
Section: Intorudctionmentioning
confidence: 99%
“…However, Granata et al showed no radiological pattern differences among VoC in another retrospective study. Actually, they considered also vaccination as a confounding factor but they enrolled only ICU patients and they did not refer to the clinical history of COVID-19 [22]. In our opinion, this should be considered a bias as only severe cases were hospitalized in ICU.…”
Section: N Resultsmentioning
confidence: 99%
“…The number of patients with patchy consolidation shadows (14.62%), pleural changes (10.77%), and two or more abnormal signs (30.3%) was higher in the low Ct group than in the other two groups (all P < 0.05). Overall, Omicron infection showed fewer signs of pulmonary consolidation than other SARS-CoV-2 variant infections[ 23 ]. Consolidation shadows may result from vasculitis, hemorrhage, and peripheral serous exudation caused by high viral loads attacking blood vessels, secondary or direct alveolar inflammation, massive immune cell filling, and small airway mucus plugs.…”
Section: Discussionmentioning
confidence: 99%